Role Artificial Intelligence (AI) in Forecasting and Planning Management of Pharmaceutical Procurement in Pharmacies - Gede Trima Yasa; Made Prita Artika (Indonesian Journal of Global Health Research, 2025)
The rapid development of Artificial Intelligence (AI) has permeated various aspects of life, including the healthcare sector. In pharmacies, the adoption of AI is critical for enhancing operational efficiency and addressing common issues such as drug shortages and excess inventory. This study was conducted to evaluate the effectiveness of AI technology in the forecasting and planning processes of pharmaceutical procurement. This study employed a quantitative research design using a quasi-experimental method. A purposive sampling method was used to select ten pharmacies that still rely on conventional methods for pharmaceutical forecasting and procurement. Total 30 respondents were included. This study's primary instrument was a questionnaire. This study utilized primary data, which was collected directly from the research respondents. A Mann-Whitney U test was performed to assess the significance of AI use in forecasting and planning pharmaceutical procurement. The results showed a significant difference between the control group (mean rank = 11.45) and the treatment group (mean rank = 29.55). The test statistic was U = 19.0 with a significance value of p < 0.001, indicating that AI significantly improves the accuracy of procurement forecasting and planning. Furthermore, user satisfaction with the AI application was high, with 57.14% of respondents strongly agreeing and 42.86% agreeing that the technology facilitates the procurement process.